Injectivity Classes of the Pompeiu Transformation - Ochakovskaya, O. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
New conditions for the injectivity of the Pompeiu transform for integral ball means are obtained. The main results substantially improve some known uniqueness theorems for functions with vanishing integrals over balls of fixed radius.